1994
DOI: 10.1002/dc.2840100304
|View full text |Cite
|
Sign up to set email alerts
|

Paranuclear blue inclusions in small cell undifferentiated carcinoma: A diagnostically useful finding demonstrated in fine‐needle aspiration biopsy smears

Abstract: In a study of bone marrow aspiration smears, Wittchow et al. (Mod Pathol 1992;5:555-558) described a highly characteristic finding, paranuclear blue inclusions (PBIs), found almost exclusively in cases of metastatic small cell undifferentiated carcinoma (SCUC). PBIs are 1-4 microns, light blue, cytoplasmic inclusions best visualized with Romanowsky-type stains. These inclusions are most easily found indenting the nuclei within clusters of closely opposed tumor cells. In the current study air-dried fine-needle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
2
12
2
Order By: Relevance
“…In addition to these cytologic features, some tumor cells had PBIs in the cytoplasm in our case. This finding was identical to that seen in air-dried fine needle aspiration biopsy (FNAB) smears from 146 primary and metastatic small cell and non-small cell malignancies of adulthood and childhood reported by Walker et al 15 They concluded that the presence of PBIs in air-dried FNAB smears of adult neoplasms, while not pathognomonic of small cell carcinoma, was diagnostically useful. Wittchow et al 16 also reported that PBIs were identified in 40 of 47 (85%) cases of metastatic small cell carcinoma on air-dried bone marrow aspirates stained with Wright's stain.…”
Section: Discussionsupporting
confidence: 66%
“…In addition to these cytologic features, some tumor cells had PBIs in the cytoplasm in our case. This finding was identical to that seen in air-dried fine needle aspiration biopsy (FNAB) smears from 146 primary and metastatic small cell and non-small cell malignancies of adulthood and childhood reported by Walker et al 15 They concluded that the presence of PBIs in air-dried FNAB smears of adult neoplasms, while not pathognomonic of small cell carcinoma, was diagnostically useful. Wittchow et al 16 also reported that PBIs were identified in 40 of 47 (85%) cases of metastatic small cell carcinoma on air-dried bone marrow aspirates stained with Wright's stain.…”
Section: Discussionsupporting
confidence: 66%
“…It is unclear whether PNIs, especially the target inclusions, are the same as paranuclear blue inclusions (PBIs), also known as blue bodies, 20 which are best visualized on air-dried smears stained with Romanowsky-type stains and are commonly observed in small cell undifferentiated carcinomas (SCUCs) of lung. [21][22][23] PBIs are reported not to be demonstrable on alcohol-fixed, H-E-stained cytologic smears. 23 CVs were more frequently seen in the LC/A variant (> 60% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…21,24,34 PBIs are 1-4-µm, spherical cellular inclusions demonstrated by Romanowsky-stained FNA biopsy material and may represent phagocytosed nuclear/cytoplasmic material (apoptotic bodies). 38 The "intermediate filament buttons," which are present as pale pink, homogeneous, dense, wellcircumscribed round or oval structures in the perinuclear region of cells in neuroendocrine (Merkel cell) carcinoma of the skin, 8 may pose a differential diagnostic problem. However, they can easily be distinguished from PBIs, which invariably occur singly and range from glassy light grey blue to dark blue.…”
Section: Discussionmentioning
confidence: 99%
“…1 A review of the literature shows that the various cytomorphologic features that could be useful in the diagnosis of SRCT are rosettes and filamentous/fibrillar matrix in neuroblastoma, tubule formation in nephroblastoma, tadpole cells in rhabdomyosarcoma and neuroblastoma, PAS-positive inclusions in Ewing's sarcoma, nuclear grooves in histiocytosis X, noncohesive cells in lymphoma and histiocytosis X, lymphoglandular bodies in NHL, and nuclear molding and PBIs in small cell anaplastic carcinoma. 2,3,12,21,25,31,34,38 Most of these studies were based on either assessment of multiple cytomorphologic characteristics in a specific subtype of SRCT 2,3,24,34 or a single cytomorphologic feature in various SRCTs. 25,38 In the present study an attempt was made to critically assess the role of 12 cytomorphologic features in the diagnosis of specif- The rosettes observed in neuroblastoma and ganglioneuroblastoma have been referred to as "Homer-Wright" rosettes 20,24,34 or pseudorosettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation